PENYEDIAAN PENDIDIKAN INKLUSIF SEKOLAH DASAR PERSPEKTIF KESETARAAN NILAI UTILITARIANISME JOHN STUART MILL - Nur Alifah (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
ABSTRACT Education can be said to be a basic right in addition to the right to life and the right to freedom to support the fulfilment of other human rights. Inclusive education is a teaching and learning process where students with disabilities learn alongside non-disabled students in mainstream schools with modified curriculum and learning according to the students' abilities. John Stuart Mill, as a Utilitarian, has contributed ideas related to the realisation of equal access for each individual, including the right to education. This research uses the Library Research method, which uses library literature such as books, journals, and articles as primary and secondary sources. The research also includes literature that has links to the field of law as the object of research on the provision of educational equality. The urgency of this research is as an effort to create a space for discussion that is expected to spark a wider and more equitable application of the provision of inclusive education. The results of the study state that, Equality in Mill's utilitarian conception leads to equality of opportunities owned by each individual in fulfilling their rights. This opportunity does not focus on the economy, but the main rights of humans themselves in voicing opinions or getting an education. Education in Mill's utilitarian conception is an instrument to improve the welfare and happiness of society as a whole. Equality in access to education is considered an important step towards achieving greater happiness for individuals and society. This is in line with efforts to provide inclusive education at the primary school (SD) level as SD is the main compulsory gateway to early education. Keywords: Disability; Equality; Education;John Stuart Mill; Utilitarianism ABSTRAK Pendidikan dapat dikatakan sebagai basic right disamping hak hidup dan hak kebebasan untuk menunjang pemenuhan hak asasi manusia lainnya. Pendidikan inklusif adalah proses belajar mengajar dimana siswa penyandang disabilitas belajar bersama siswa non disabilitas di sekolah umum dengan modifikasi kurikulum dan pembelajaran sesuai dengan kemampuan siswa. John Stuart Mill, sebagai seorang Utilitarian, memiliki andil gagasan terkait erwujudan kesetaraan akses bagi tiap individu, termasuk hak dalam mengenyam pendidikan. Penelitian ini menggunakan metode kepustakaan (Library Research), yang menggunakan literatur perpustakaan seperti buku, jurnal, dan artikel sebagai sumber primer dan sekunder. Penelitian juga mencakup kepustakaan yang memiliki kaitan dengan bidang hukum sebagaimana objek penelitian penyediaan kesetaraan pendidikan. Urgensi penelitian ini adalah sebagai salah satu upaya penciptaan ruang diskusi yang diharapkan dapat memantik aplikasi penyediaan pendidikan inklusi yang lebih luas dan merata. Adapun hasil penelitian menyatakan bahwa, Kesetaraan dalam konsepsi utilitarian Mill mengarah pada kesetaraan akan peluang yang dimiliki oleh setiap individu dalam memenuhi hak nya. Peluang ini bukan berfokus pada ekonomi, melainkan hak utama dari manusia sendiri dalam menyuarakan pendapat ataupun mengenyam pendidikan. Pendidikan dalam konsepsi utilitarian mill sebagai instrumen untuk meningkatkan kesejahteraan dan kebahagiaan masyarakat secara keseluruhan. Kesetaraan dalam akses pendidikan dianggap sebagai langkah penting untuk mencapai kebahagiaan yang lebih besar bagi individu dan masyarakat. Hal ini sejalan dengan upaya penyediaan pendidikan inklusif jenjang Sekolah Dasar (SD) sebagaimana SD merupakan gerbang wajib utama pendidikan bermula. Kata Kunci: Disabilitas; John Stuart Mill; Kesetaraan; Pendidikan; Utilitarianisme